Why Personal Characteristics of Innovative Leadership Can Drive Organizational Competitive Advantage? A Literature Review with Integrative Approach - Asrarudin - Asrarudin (Jurnal Administrasi Bisnis, 2023)
This research is qualitative research that investigates the multi-characteristics of innovative leadership that drives the organization's competitive advantage by applying an integrative review of literature approach. Data and information are adopted from research outputs published in indexed and reputable journals in 2012-2021. Based on several articles reviewed the author found that there are three core competencies of innovative leaders: managerial, conceptual and team-building skills. These embedded competencies can shape innovative attitude and behaviour of subordinates which consistently and sustainably will enhance individual and collective productivity.   In the long term it can boost organizational competencies in all level of management hierarchy. Personal characteristics of innovative leader consist of (1) clear and strong vision; (2) consistent integrity; (3) partnership working; (4) two-way communication; (5) managing uncertain changing environments; (6) thinking creatively and innovatively; (7) understand the issues comprehensively; (8) problems solving; (9) positive and energetic thinking; (10) mental health stability; and (11) adequate physical health. In principle, personal characteristics of characteristic of innovative leader consist of hard and soft personal unique competencies. The results of this research study reveal that the personal characteristics of innovative leadership as a role model are able to build subordinates' innovative behaviour which is consistently and continuously able to increase the organization's competitive advantage.